(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
The Establishment of the Rahad Agricultural Scheme in Eastern Sudan in the 1970s established an agricultural innovation system where different actors are networking to provide better livelihoods within the irrigated scheme area. The objectives of the paper are presenting the connections of women groups and their networking to the extension and finance institutions in the scheme area and trying to relate it to the theorizing of agriculture knowledge and information system, so new roles and connections are suggested to improve the performance of Rahad Agricultural Scheme. System thinking is the methodology to analyze knowledge networking among extension, and finance institutions from one side and among women’s groups on other side. Accordingly, Rapid Appraisal of Agricultural Knowledge Systems (RAAKS) and Social Network Analysis were conducted to identify roles and knowledge sharing among Women Groups, Saving and Social Development Bank and Extension Administration in Rahad Agricultural Scheme. Results of this research showed that most Women Associations interviewed had a sense of independence from the Women’s Union activities, while the Women’s Union expressed closer connections and had a sense of ownership over the Women’s Associations activities such as saving funds and Quran learning lessons. Some Women Groups in Rahad Agricultural Scheme are actively engaged in non -farming micro-finance projects through their connections with Saving and Social Development Bank. However, their farming and livestock keeping activities are not recognized by Extension Administration in the scheme and not financed by the schemes finance institutions. Building of multi hubs model (connecting actors with training and capacity building) is the strategy to improve knowledge networking between women’s groups, Extension Administration and Saving and Social Development Bank. In this manner, the extension can be the knowledge broker who can connect actors and communicate information in order to improve the networking among the studied actors which would enhance the performance of agricultural innovations in Rahad Agricultural Scheme as a whole